2008
DOI: 10.1158/0008-5472.can-07-2696
|View full text |Cite
|
Sign up to set email alerts
|

A Role for TAZ in Migration, Invasion, and Tumorigenesis of Breast Cancer Cells

Abstract: TAZ (WWTR1), identified as a 14-3-3 binding protein with a PDZ binding motif, modulates mesenchymal stem cell differentiation. We now show that TAZ plays a critical role in the migration, invasion, and tumorigenesis of breast cancer cells. TAZ is conspicuously expressed in human breast cancer cell lines in which its expression levels generally correlate with the invasiveness of cancer cells. Overexpression of TAZ in lowexpressing MCF10A cells causes morphologic changes characteristic of cell transformation and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
469
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(501 citation statements)
references
References 22 publications
22
469
1
1
Order By: Relevance
“…34 Hence, it would appear that TAZ is a potent activator of cell transformation and tumorigenesis. 35,36 On the basis of this evidence, and given the importance of epithelial to mesenchymal transition and stemness in the carcinogenesis of certain subtypes of endometrial tumors, 3,4 we analyzed TAZ expression in a series of 143 endometrial carcinoma samples. We found that TAZ expression was associated with high-grade endometrial tumors, mainly represented by undifferentiated endometrial carcinomas and endometrial carcinosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…34 Hence, it would appear that TAZ is a potent activator of cell transformation and tumorigenesis. 35,36 On the basis of this evidence, and given the importance of epithelial to mesenchymal transition and stemness in the carcinogenesis of certain subtypes of endometrial tumors, 3,4 we analyzed TAZ expression in a series of 143 endometrial carcinoma samples. We found that TAZ expression was associated with high-grade endometrial tumors, mainly represented by undifferentiated endometrial carcinomas and endometrial carcinosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genomic amplification and elevated expression and nuclear localization of YAP has been observed in human cancers (Overholtzer et al, 2006;Zender et al, 2006;Dong et al, 2007;Zhao et al, 2007;Steinhardt et al, 2008;Hall et al, 2010). Overexpression of TAZ has also been noted in human breast cancer samples and non-small cell lung cancer cell lines (Chan et al, 2008;Zhou et al, 2011b). Similar to YAP overexpression, ablation of the Hippo pathway components Mer and Sav and double knockout of Mst1/2 in mice result in liver enlargement and tumor formation characteristic of HCC and cholangiocarcinoma (CC) (Zhou et al, 2009;Benhamouche et al, 2010;Lee et al, 2010;Lu et al, 2010;Song et al, 2010;.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…Of particular interest to this study is the mammary gland. Although several studies have implicated dysregulation of the Hippo pathway in breast cancers (Overholtzer et al 2006;Chan et al 2008;Lei et al 2008;Cordenonsi et al 2011), its physiological role in mammary gland development is unknown. Even in breast tumorigenesis, the contribution of Hippo signaling is controversial.…”
mentioning
confidence: 99%